KEWIRAUSAHAAN DENGAN MENGGUNAKAN TEKNIK BISNIS ON LINE DI ORMAS KRN DEPOK - Petrus Ridaryanto; Sinta Boentoro; A. S. Marsudi (PROSIDING SERINA, 2021)
The development of the use of information technology by the people in Indonesia by using internet media currently greatly affects various sectors of social activities, including trading activities. Buying and selling activities carried out by the community today are referred to as on-line/online business activities. In online business activities, buyers only need to identify products, orders and payments via the internet, so this will make it more efficient for the buyer because it does not require transportation costs to go to the market or to the seller's shop, as well as this will also benefit the producer. or sellers because they no longer need to rent a place to sell their products.   Currently, online business activities have been carried out by traders or producers of medium and large size. However, for small and micro-sized entrepreneurs, there are still many who have not been able to adjust to doing online business, as is the case with small entrepreneurs who join the National People's Coalition Mass Organization (Ormas KRN) Depok City, almost all of them have not used the internet media for their business activities. This condition resulted in a decrease in their sales turnover. Departing from this condition, the community service team at the Faculty of Economics and Business Atma Jaya Unika collaborated with the KRN Ormas to conduct entrepreneurial training activities using internet media to carry out their business activities called online business techniques, with the aim that entrepreneurs who are members of the KRN Ormas can start using the media. internet to sell their merchandise. The activity was carried out on June 12, 2021, which was attended by 17 small entrepreneurs. The training method is the lecture method, question and answer and discussion as well as visualization of the use of several online business techniques. To ensure follow-up on the implementation of online business activities for entrepreneurs who are members of the KRN Ormas, the community service team at the Faculty of Economics and Business Atma Jaya University provides assistance opportunities to implement online business programs through online telecommunications.